PREDICTIVE FACTORS OF MORBIDITY ASSOCIATED WITH ESOPHAGEAL VARICEAL BLEEDING IN CHILDREN WITH PORTAL HYPERTENSION - Maria Carolina Feres de Lima Rocha GAMA; Eleonora Druve Tavares FAGUNDES; Thaís Costa Nascentes QUEIROZ; Adriana Teixeira RODRIGUES; Luiza Caroline VIEIRA; Alexandre Rodrigues FERREIRA (Arquivos de Gastroenterologia, 2023)
ABSTRACT Background: Most data on the natural history of portal hypertension come from studies in adults. The morbidity rate of upper gastrointestinal bleeding (UGIB) in children with portal hypertension has not been systematically characterized. Objective: To describe the morbidity and mortality of UGIB in pediatric patients with portal hypertension and identify predictive factors for the occurrence of its main complications. Methods: This retrospective study included pediatric patients with cirrhotic portal hypertension or with extrahepatic portal vein obstruction (EHPVO). Mortality and UGIB complications within a period of up to 6 weeks of the bleeding were investigated. To determine the predictive factors of morbidity, a multivariate analysis was performed using logistic regression; all results were considered significant at P<0.05. Results: A total of 86 patients (51.2% with EHPVO and 48.8% with cirrhosis) had 174 bleeding events. Ascites was the most common complication (43.1% of all cases), being more prevalent in patients with cirrhosis (P<0.001). Cirrhosis was a predictor of the occurrence of any morbidity (OR 20.3). The need for blood transfusion was predictor of at least one complication (OR 5.8), ascites (OR 7.2) and infections (OR 3.8) in the general group and at least one complication (OR 11.3) and ascites (OR 5.8) in cirrhotic patients. The need for expansion was a predictor of any morbidity (OR 4.6) and infections (OR 3.9) in the general group, in addition to being predictor of infection in cirrhotic patients (OR 5.4). There were no deaths from UGIB in the six weeks post-bleeding. Conclusion: The study showed the relevance of morbidity after UGIB in pediatric patients with portal hypertension, especially in those with cirrhosis. The patients with hemodynamic instability requiring blood transfusion or expansion on admission are at increased risk of complications related to upper gastrointestinal bleeding and should be closely monitored.